Dynamics Analysis of High-speed Parallel Robot based on Screw Theory - Pu Wu; Zongyan Wang; Xiao He; Hongxiang Jing; Changlin Xia (Jixie chuandong)
In order to improve the accuracy and stability of the robot in the process of high-speed motion， the method of modeling the dynamic equation of the 4-DOF Delta high-speed parallel robot is studied. The geometrical method is used to solve the inverse kinematics equation of the robot， and the Kane method of screw theory is combined to establish the dynamic equation of the robot. Matlab programming is used to solve the kinematics and dynamics models， and the displacement， velocity， acceleration and torque curves of the driving arm are drawn. The dynamics control system of the Delta robot is established in Simscape， and the displacement curve of the driving arm is obtained with torque as input. Comparing the calculation and simulation results， the correctness of the dynamic equation is verified.